PENGARUH SOCIAL INTERACTIVITY ANTARA CUSTOMER ENGAGEMENT BEHAVIOR DAN BRAND LOYALTY - Muhammad Angga Maulana; Nabila Armeinita; Renny Risqiani (Universitas Kuningan, 2023)
AbstractThe study aims to examine the effect of social interactivity between customer engagement behavior and brand loyalty on social media. This research uses a type of quantitative approach. The research method is in the form of a survey using primary data collected by filling out a closed questionnaire using a Likert scale of 1-5. Sampling used purposive sampling with the respondent's criteria, namely Facebook social media users aged 17-30 years. Total respondents who were sampled in this study were 135 active Facebook users. This research was conducted using Structural Equation Modeling (SEM) and processed with the help of SPSS and AMOS software. The results of the study show that (1) Customer Engagement Behavior has a positive effect on company Brand Loyalty on page content on the Facebook social media platform. (2) Customer Engagement Behavior has a positive effect on company Social Interactivity on page content on the Facebook social media platform. (3) Social Interactivity has no positive effect on company Brand Loyalty on page content on the Facebook social media platform.Keywords: social interactivity; customer engagement behavior; brand loyaltyAbstrakPenelitian bertujuan menguji pengaruh social interactivity antara customer engagement behavior dan brand loyalty di media sosial. Penelitian ini menggunakan jenis pendekatan kuantitatif. Metode penelitian dalam bentuk survey menggunakan data primer yang dikumpulkan melalui pengisian kuesioner tertutup menggunakan skala Likert 1-5. Pengambilan sampel menggunakan purposive sampling dengan kriteria responden yaitu pengguna media sosial Facebook berusia 17-30 tahun. Total responden yang menjadi sampel dalam penelitian ini adalah 135 orang pengguna aktif facebook. Penelitian ini dilakukan dengan menggunakan Structural Equation Modelling (SEM) dan diolah dengan bantuan Software SPSS dan AMOS. Hasil penelitian menunjukkan bahwa (1) Customer Engagement Behavior berpengaruh positif terhadap Brand Loyalty perusahaan terhadap konten halaman di platform media sosial facebook. (2) Customer Engagement Behavior berpengaruh positif terhadap Social Interactivity perusahaan terhadap konten halaman di platform media sosial facebook. (3) Social Interactivity tidak berpengaruh positif terhadap Brand Loyalty perusahaan terhadap konten halaman di platform media sosial facebook.Kata kunci: social interactivity; customer engagement behavior; brand loyalty